Efficacy and tolerability of EPs 7630 in patients (aged 6-18 years old) with acute bronchitis - Kamin, Wolfgang; Maydannik, Vg; Malek, F. A.; Kieser, Meinhard (Acta paediatrica, 2010)
For EPs-7630, a herbal drug preparation from Pelargonium sidoides roots, therapeutic effects in respiratory tract infections outside the strict indication for antibiotics have already been demonstrated in adults. Now, a dose-finding study for EPs-7630 was performed in children and adolescents.